Curriculum Management In Kapau Islamic Boarding Schools - Agustin, Rini; Al Kadri, Hanif (Universitas Negeri Padang, 2023)
The problem in this study is related to the process of managing the curriculum and organizing the curriculum at Kapau Islamic Boarding School which has not been well planned, the level of supervision over curriculum management at Kapau Islamic Boarding School is still low. The purpose of this research is to look at curriculum management at Kapau Islamic Boarding School. This research is in the form of qualitative description. The research was conducted at the Islamic Boarding School Tarbiyah Ilamiyah Kapau Tilatang Kamang Kab. Agam. The techniques used to collect data in this study are observation, documentation, interviews. The results of the study show that Curriculum Management at Kapau Islamic Boarding School goes through a process or framework, which involves all institutional structures at Kapau Islamic Boarding School which are guided by the vision and mission of education, curriculum components, curriculum organization, curriculum implementation and control of curriculum implementation. Implementation of the curriculum at Kapau Islamic Boarding School uses two curriculum models, namely the madrasah curriculum which refers to the curriculum of the Ministry of Religion, and a special cottage curriculum for cottage lessons. The two curricula run separately in the education system at Kapau Islamic Boarding School. The madrasah curriculum is systematized, has documents and develops with reference to Islamic education curriculum standards from the Ministry of Religion, while the pondok (religious) curriculum refers to the teaching of kiyai/sheikh and does not have written curriculum documents using yellow books. So that the implementation and organization of the curriculum at Kapau Islamic Boarding School integrates one subject with another